Comparative Test of the Effect of X-Ray Tube Current Analysis and Exposure Time on CR (Computed Radiography) Image Quality - Diah Rahayu Ningtias; Bayu Wahyudi; Imam Tri Harsoyo (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
The medical image system in the form of digital examination results using Computed Radiography (CR) needs to be analyzed, this can be done by knowing the quality of the image contrast resolution and the quality of its spatial resolution. This study conducted a comparative test between two methods of analyzing contrast resolution of medical images. Image quality on Computed Radiography can be determined using contrast resolution analysis, namely calculating the CNR value and PSNR value. The study was carried out using a phantom to represent the density of the bone. The voltages used are 50 kV, 60 kV, 70 kV and 81 kV, respectively. With each voltage, the tube current and exposure time (mAs) were varied 1.6 mAs, 2 mAs, 4 mAs, 8 mAs, 16 mAs, and 32 mAs. The higher the CNR value obtained, the better the image quality. While the PSNR value to get the optimal quality of medical image contrast, the current-time variation of 4 mAs and 16 mAs must be used. Due to the time-current variation, a high PSNR value is obtained, which indicates that the noise of the medical image is getting smaller so that a good contrast quality of the medical image is obtained. Both of these methods can be used to test the suitability of X-ray device, especially for quality control of medical images